Experimental Study on the Effect of Insertion of Copper Lessing Rings in Phase Change Material (PCM) on the Performance of Thermal Energy Storage Unit - Albaldawi, Rafa A.H; Shyaa, Aseel K.; Hammendy, Ban M.H. (Al-Khwarizmi Engineering Journal, 2015)
Abstract One of the most suitable materials to be used in latent heat thermal energy storage system (LHTES) are Phase change materials, but a problem of slow melting and solidification processes made many researchers focusing on how to improve their thermal properties. This experimental work concerned with the enhancing of thermal conductivity of phase change material. The enhancing method was by the addition of copper Lessing rings in phase change material (paraffin wax). The effect of diameter for the used rings was studied by using two different diameters (0.5 cm and 1cm). Also, three volumetric percentages of rings addition (3%, 6% and 10%) were tested for each diameter. The discharging process was done with four velocities for each case. The obtained results indicated that the maximum volumetric percentage gave a diminished time for melting and maximized the heat transfer in both PCM and air sides as compare with the case of no rings, but the effect of these rings had lower effect on the solidification time. In case of 1 cm rings diameter minimum time for melting was obtained for both 3% and 6% volumetric percentages as compared with the same percentages in case of 0.5 cm diameter rings, while the latter with 10% volumetric percentage overcomes the 1 cm diameter rings for the same previous percentage. Also it can be seen that the minimum velocity (v=1m/s) gave the utmost outlet temperature and with the maximum one (v=3m/s), the minimum solidification time achieved. Keyword: Thermal energy storage systems, Latent heat storage, Phase change materials, Heat transfer enhancement.